EVALUATION OF THE USE OF HEPATOPROTECTORSIN PATIENTS WITH CHRONIC VIRAL HEPATITIS B. - Yakubova Nigina Sadriddinovna (Web of Journals Publishing, 2024)
According to WHO data, over the past 20 years, there has been a trend towards an increase in the number of liver diseases that cause high mortality in the population [3]. 107 patients diagnosed with CHB were under observation. All patients underwent a method for quantitative determination of HBV viral load by PCR. The level of liver fibrosis was also determined by a non-invasive method - fibroscanning. As a hepatoprotective therapy, patients were prescribed.